An introduction to nature of care - Manuel Jesús Salas Iglesias (Universidad de Alicante, 2012)
This document analyses the biological and cultural nature of Care, explaining to which extent innate and learned principles can be found in it. As a result, apart from highlighting its precise and universally accepted dimension as an activity of attention or assistance applying to the animal world and essential for survival, a need is proven for resorting to an abstract dimension according to the demands inherent to its complexity. Furthermore, this analysis reveals that the notion of Care not only refers to an act in itself but a phenomenon within reality, exclusively human and universal. This work concludes with new considerations for the sciences that understand Care as an unfailing part of its object of study.